Preparation and characterization of electrically conductive films from native sago starch - Sim, Lisa Siew Onn (Universiti Malaysia Sarawak, UNIMAS, 2013)
In this study, electrically conductive biopolymer film have been developed using native sago starch as the main precursor material. Native sago starch is a locally produced biopolymer which is easily available, cheap, non-toxic and biodegradable. The morphology and chemical structures of the starch-based films was characterized by using Scanning Electron Microscopy (SEM), Fourier Transformed Infrared Spectroscopy respectively and Atomic Absorption Spectroscopy. The electrical conductivity of starch-based films was determined by a multimeter. The potential applications of these electrically conductive starch-based films were evaluated.